Bias deployable grids with horizontal compound scissor-like elements: A geometric study of the folding/deployment process. Issue 1 (March 2022) - Freire-Tellado, Manuel J; Muñoz-Vidal, Manuel; Pérez-Valcárcel, Juan
Bias deployable structural units are two-way structures arranged in a rotational pattern with respect to the edges. They have interesting advantages such as robust three-dimensional operation with supports around their entire base perimeter and the exclusive use of load-bearing scissor-like elements (SLEs). However, they do not have edge trims and their resistance to angular distortion is limited. This article proposes a series of deployable bi-stable structures that address these problems and incorporate new, resilient features. A method of analysing the incompatibilities of the structural unit is developed based solely on the geometric study of the deployment process, which allows the level of incompatibility of the proposal to be graduated, varying from stress-free structures to bi-stable structures. A kinematic model of one of the proposals allows the research undertaken to be contrasted.